The Correlation between English Reading Habit and English Reading Comprehension for EFL Students - Stevi Indarti Andriani; Ariyanti (Borneo Educational Journal (Borju), 2022)
This research focused in Reading Habit and Reading Comprehension in students' English ability in second grade. The result of data obtained from SMP Negeri 26 Samarinda second grade. There were four classes in second grade, while the number of each class is 32 students. Thus, there were 128 populations in second grade. For this research, the researcher used correlation technique quantitative analysis and simple random sampling to choose the sample until consists of 35 subjects as samples. The instruments used are the questionnaire and reading test. The researcher used a questionnaire and reading test with reading text and questions that the researcher has a choice after the researcher knowing how far skill reading text in second grade and how much valid the result from per question in try out test at Class 8A as the first research. And then, the researcher used a population of Class 8B, 8C, and 8D as secondary research for the tested questionnaire and reading test. There were 35 students chosen as the subject. The result from the correlation test is counted low negative correlation result (-0,358) with sig. p-value <0,05 (0,035). Based on the result of the tests, Ha Hypothesis is accepted and Ho Hypothesis is rejected. Keywords: reading habit; reading comprehension